SEVEN DIMENSIONS OF LEARNING CULTURE: ENHANCING PUBLIC HEALTH PRACTICE THROUGH FORMAL LEARNING (Proceedings of the International Conference on Public Health, 2017)
Continuing Professional Education (CPE) is entering the third era in which education and learning occur in a workplace. The concept of learning in the profession is believed to lead to the improvement of job performance of public health professionals. However, little research has been carried out to gain insight into the motivation to enhance professional development through formal education opportunities in the workplace. This study aims at understanding participation in professional development of public health professionals to enhance their professional development.  All data were collected using online survey to public health professionals in the database of The Georgia of Public Health TrainingCenter (GPHTC). The results ofthe study suggests that most public health professionals participated in available formal learning opportunities in their organization to advance in their professions. The type of the formal learning opportunities and the reason for participation was varies depending on the type of organization. In addition, the results of the study also indicate that the participants mostly considered the learning culture in their organization as high at individual, team/group, and organizational level.
Keywords: Public health professionals, Formal learning, Continuing professional education